Colder is better during hypothermic circulatory arrest for acute type a aortic dissection. (April 2013) - Legras, Antoine; Bruzzi, Matthieu; Nakashima, Kuniki; Hillion, Marie-Line; Loisance, Daniel; Kirsch, Matthias
Abstract Objectives. To evaluate the influence, on early postoperative outcomes, of temperature during hypothermic circulatory arrest in emergent surgery for acute type A aortic dissection. Design. Hypothermic circulatory arrest (HCA) with antegrade cerebral perfusion was performed in 63 patients who underwent emergent surgery for acute type A aortic dissection between 2000 and 2009. Patients were retrospectively separated in two groups: (1) deep HCA, lowest nasopharyngeal temperature < 17°C (n = 29; 46%) and (2) moderate HCA, lowest nasopharyngeal temperature ≥ 17°C (n = 34; 54%). Results. Hospital mortality reached 27%. The nasopharyngeal temperature did not influence postoperative mortality or neurological outcome. Patients with deep HCA had significantly lower rate of infection (33% vs 69%; p = 0.009) and shorter median intensive care unit length of stay (4 days (17) vs 15.5 days (26) p = 0.017). Multiple regression analysis revealed that the lowest nasopharyngeal temperature was the only significant variable associated with intensive care unit length of stay (p = 0.005). Conclusions. Patients suffering from acute type A aortic dissection might benefit from colder hypothermia during circulatory arrest.